2012
DOI: 10.1111/j.1365-2893.2011.01553.x
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin 28B polymorphisms are the only common genetic variants associated with low‐density lipoprotein cholesterol (LDL‐C) in genotype‐1 chronic hepatitis C and determine the association between LDL‐C and treatment response

Abstract: Summary Low-density lipoprotein cholesterol (LDL-C) levels and interleukin 28B (IL28B) polymorphism are associated with sustained viral response (SVR) to peginterferon/ribavirin (pegIFN/RBV) for chronic hepatitis C (CHC) infection. IL28B has been linked with LDL-C levels using a candidate gene approach, but it is not known whether other genetic variants are associated with LDL-C, nor how these factors definitively affect SVR. We assessed genetic predictors of serum lipid and triglyceride levels in 1604 patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 34 publications
(56 reference statements)
2
26
0
1
Order By: Relevance
“…IL28B polymorphisms influence SVR rates in HCV genotypes 1 and 4 , although its effect in genotypes 2 and 3, which generally respond more favourably to therapy, is less obvious . IL28B genotypes also have associations with hepatic steatosis , post‐transplant re‐infection rates , and serum cholesterol levels . Other noteworthy SNPs identified by GWAS related to HCV therapeutics are the inosine triphosphatase (ITPA) gene polymorphisms on chromosome 20, which protect against ribavirin‐related hemolytic anaemia .…”
Section: Introductionmentioning
confidence: 99%
“…IL28B polymorphisms influence SVR rates in HCV genotypes 1 and 4 , although its effect in genotypes 2 and 3, which generally respond more favourably to therapy, is less obvious . IL28B genotypes also have associations with hepatic steatosis , post‐transplant re‐infection rates , and serum cholesterol levels . Other noteworthy SNPs identified by GWAS related to HCV therapeutics are the inosine triphosphatase (ITPA) gene polymorphisms on chromosome 20, which protect against ribavirin‐related hemolytic anaemia .…”
Section: Introductionmentioning
confidence: 99%
“…Amino acid 70 substitution in the core region and LDL-cholesterol level have already been shown to be predictive factors of SVR to PEG-IFN plus ribavirin therapy 17. In addition, it has been reported that a high serum level of LDL-cholesterol is linked to the IL-28B major allele 18,19. Regarding AFP, it has been reported that AFP level is an independent factor for response to triple therapy of telaprevir, PEG-IFN, and ribavirin in previous nonresponders to PEG-IFN plus ribavirin therapy 20.…”
Section: Discussionmentioning
confidence: 99%
“…In a study on HCV G1, distortion of lipoprotein metabolism was more profound in patients who were non-favorable responders, and decreases of LDL-C, HDL-C, and TG were reported using conventional measurement technologies (26). However, after the discovery of rs8099917 and rs12979860 near the human IL28B gene as a strong host factor affecting the response to peg-IFN plus RBV therapy (27, 28), the significance of lipid profiles on predicting SVR was thought to be doubtful because the power of the IL28B genotype for predicting the efficacy of peg-IFN plus RBV therapy was so strong (29, 30). In the present study, we found that the C/T ratio in fasting serum VLDL was independently associated with SVR along with the IL28B genotype in patients with chronic HCV G1b who were treated with peg-IFNα-2b plus RBV.…”
Section: Discussionmentioning
confidence: 99%